Minimalism [videorecording (DVD)] : a documentary about the important things - Millburn, Joshua Fields; Nicodemus, Ryan (Catalyst, 2016)
How might your life be better with less? Minimalism examines the many flavors of minimalism by taking the audience inside the lives of minimalists from all walks of life--families, entrepreneurs, architects, artists, journalists, scientists, and even a former Wall Street broker--all of whom are striving to live a meaningful life with less.